• Предмет: Алгебра
  • Автор: madike
  • Вопрос задан 7 лет назад

ПОМОГИТЕ!!!Сделаю лучшим ответом,если напишите с решением!
Упростите выражение:
1)(12х²+9x):(3x)+(6x³-3x²):x²
2)-(4а²-3а):а+(8а³-4а²):(2а²)
3)(8у³-5ху²):у²+(х²у-3ху²):(0,5ху)
4)-(2х²у+х²у):(0,5ху)+(6х³-2х²у):х²
Ответы на 1,2,4 примеры:10х=1=-2у

Ответы

Ответ дал: Rinalav18
0
1) (12х²+9x):(3x)+(6x³-3x²):x²=3х*(4х+3):3х+3х^2*(2х-1):х^2=
4x+3+3*(2x-1)=4x+3+6x-3=10x
2) -(4а²-3а):а+(8а³-4а²):(2а²)=-a*(-4a+3):а+4а^2*(2a-1):2а^2=4a-3+4a-2=8a-5
3) (8у³-5ху²):у²+(х²у-3ху²):(0,5ху)=y^2*(8y-5x):y^2+xy*(x-3y):0,5xy=8y-5x:0,5+x-3y:0,5=y-1,5х
Похожие вопросы